Studi Ketahanan Benturan pada Komposit Serat Rami-epoksi dan Polimer Blend ABS-PP untuk Aplikasi Bahan Alternatif Soket Prostesis - Fadli Robiandi; Menasita Menasita; Ikal M (LPPM ITK, 2018)
Fabrication of rami fiber based on composite with epoxy matrixs and polymer blend of ABS-PP for alternative prosthetic soket application have been conducted. This research attemp to analyze impact resistance of rami-epoxy based on composite and polymer blend base ABS-PP. Those sample was made by hand lay up and simple hot casting methode at a temperature of 250 oC. rami-epoxy based on composite and polymer blend samples with volume fraction variation 0%, 25%, 50% and 75%. The result of charpy impact test showed an increase in impact energy along with an increase in the volume fraction of rami. In other hand, an increase in ABS volume fraction could reduce the impact energy of polymer blend samples. From impact testing result, both samples showed brittle like-structure. Broken Fiber with low fiber pull out mechanism was found out in rami-epoxy composite samples. Polymer blend samples showed pull out mechanism on ABS grain.